Kajian Supply Chain Porang Sebagai Komoditi Ekspor Unggulan Desa Mundeh, Belatungan dan Batungsel Kabupaten Tabanan Propinsi Bali - I Gede Made Subagiana; Sagung Mas Suryaniadhi; Ni Luh Made Wijayati; I Made Sarjana (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The impact of the Covid-19 has caused the sectors: tourism, trade, manufacturing industry, to experience a slump. But behind that there is still hope in the agricultural sector, where agricultural exports continue to grow 15.4% in 2020 and 16.4% in 2021. This is supported by exports of the commodity porang. Porang received full attention from President Joko Widodo, he instructed the Minister of Agriculture to make porang a mainstay export commodity. In 2020, porang exports were 20,476 tons with an export value of Rp.924.3 billion. Indonesia is only able to serve 20% of the world's porang needs. In 2020, Bali is only able to meet the export of 185 tons of porang from the total demand of 750 tons per year for China. Seeing this opportunity, the people of Mundeh, Belatungan and Batungsel villages planted porang. However, problems arise during the harvest season, many porang are not sold. Problem: How is the flow of the porang supply chain. Research Objectives: To find out the porang supply chain starting from farmers, collectors, factories and suppliers. Research Methods: Qualitative Exploratory with Supply Chain Management techniques. The results of the study indicate that there is a flow of material, information and finance from the level of farmers, middlemen, suppliers, factories and buyers.